The HOMING method: a participatory interview tool integrating Indigenous perspectives in housing research - Berghan, James; Cram, Fiona; Adcock, Anna; Tawhai, Sarah (Frontiers in Research Metrics and Analytics, 2025)
Conventional housing assessment tools often impose externally defined criteria, measuring housing quality against predetermined standards that may overlook the lived experiences and cultural values of residents. In contrast, the HOMING method is a participatory tool that centers self-determined measures of home and housing quality. Rooted in Kaupapa Māori research principles, HOMING shifts power to participants, allowing them to articulate and assess what makes a house a home based on their own lived experiences, rather than externally imposed benchmarks. The name HOMING encapsulates both “Home Of Mine”—emphasizing the deeply personal nature of home—and “housing” as an active process: what people feel, think, and do to create a home. Participants use blank wooden blocks [named Aro Rākau by a kuia (female elder)] to write or draw their own housing values, then collaboratively rank and discuss these through a hands-on process of building and assessing home characteristics. This method not only facilitates rich, nuanced understandings of home, but also aligns with decolonial research approaches by centering Indigenous and participant-led perspectives. This paper introduces the HOMING method, outlines its rationale within a Kaupapa Māori research paradigm, and presents case studies reflecting on its application. Through a collaborative reflective process, the paper explores how HOMING can expand housing research methodologies, making them more inclusive, reflexive, and culturally responsive.